1999
DOI: 10.1002/jor.1100170213
|View full text |Cite
|
Sign up to set email alerts
|

Biologic model of bone transport distraction osteogenesis and vascular response

Abstract: We developed an experimental model in the rabbit of distraction osteogenesis through bone transport that closely corresponds to the clinical use of bone transport in humans. We also applied injection angiography to study the arterial response of a limb undergoing bone transport. This model includes a proximal osteotomy and bone transport to fill in a segmental tibial diaphyseal defect. Regenerate bone formed well in the gap that was created that trailed the transport segment, and slow healing at the docking si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Bone regeneration took a longer time but the process was adaptive. A number of previous experiments had also shown the importance of blood supply for bone regeneration and osteogenic potential of bone plasty but the conditions of experiments were different [16,17]. As for clinical situations, some surgeons use bone transport over intramedullary nail to avoid wearing an external fixator for a long time during defect repair but the combination cannot accelerate distraction osteogenesis [8,9,15].…”
Section: Discussionmentioning
confidence: 99%
“…Bone regeneration took a longer time but the process was adaptive. A number of previous experiments had also shown the importance of blood supply for bone regeneration and osteogenic potential of bone plasty but the conditions of experiments were different [16,17]. As for clinical situations, some surgeons use bone transport over intramedullary nail to avoid wearing an external fixator for a long time during defect repair but the combination cannot accelerate distraction osteogenesis [8,9,15].…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit model of leg lengthening is a well-established model of distraction osteogenesis and has been used extensively to study various aspects of bone regeneration during distraction osteogenesis [6,7,11,[13][14][15][16]23,30]. Previous reports using this model have shown that the optimal rate of lengthening is between 0.7 and 1.3 mm, twice daily lengthening [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…This result is surprising and conflicts with previous research in this field. In previous studies, the angiogenic effects of distraction have been assessed by capillary density in the surrounding soft tissues (Shevtsov et al 1995, Rowe et al 1999, vascular casting of the regenerate (Choi et al 2000), histological changes in bone and soft tissues (Ilizarov 1989), arteriography (Mosheiff et al 1996, DeCoster et al 1999, and Doppler analysis of tibial and femoral arterial flows (Gil-Albarova et al 1997). These studies give evidence of increased blood flow in the soft tissues of the distracted extremity, but no evidence of increased bone blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of such an increase, however, remains weak. Proxy-parameters for blood flow such as Tc-scintigraphy, angiograms, morphological changes in blood vessels, capillary counting, and vascular casting have indicated increases in bone blood flow (Ilizarov 1989, Aronson 1994, Shevtsov et al 1995, Gil-Albarova et al 1997, DeCoster et al 1999, Rowe et al 1999, Choi et al 2000. These parameters may correlate well with the actual bone blood flow under ideal conditions, but not necessarily under conditions of inflammation and new bone formation.…”
mentioning
confidence: 99%